การพัฒนาระบบการจัดศูนย์การเรียนรู้ในสถานประกอบการ - สมชัย วรานุกูลรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To develop the learning center organization system in the workplace which consisted of the structure of learning center organization system and its components. The research methodology was research & development, composed of four phases : interviewing and studying the learning center system provided by six workplaces, developing and using focus group discussion methods related to the learning center organization system. Then, the proposed system was implemented at the two workplaces for studying the result of the organization system of the learning center. The population consisted of Human Resources Development Managers in the workplaces and employees who participated and learned from the learning systems. The research findings were as follow : 1) The organization system of the learning center in the workplace composes on three aspects : the learning center organization (learning center needs assessment, knowledge resources management), the learning process implementation (curriculum design and instructional media development, learning co-ordination and service, learning facilitation and including the condition affecting the learning outcome), and learning center evaluation (learning outcome evaluation and encourage employee to transfer their learning to the working situation, and feedback to the system. 2) Factors affecting the learning center consisted of the management supporting, self motivation of the employees, managers roles, basic facilitation, learning center officers competency, and learning resource networking.